Risk of atrial fibrillation among patients with premature ventricular complexes: a systematic review and meta-analysis of cohort studies - Rujirachun P. (2023)
INTRODUCTION: Atrial fibrillation (AF) is more likely found in patients with premature ventricular complexes (PVCs). Nonetheless, the outcomes of previous investigations remain inconclusive. To evaluate the link between PVCs and the risk of AF, we did a systematic review and meta-analysis. EVIDENCE ACQUISITION: Potentially eligible studies were found by searching for published publications indexed in the MEDLINE and EMBASE databases from inception to April 13, 2021, looking for studies that assessed the risk of AF in patients with PVCs vs. those who did not have PVCs. Dersimonian and Laird's random-effect, generic inverse variance technique was used to calculate the pooled risk ratio (RR) and 95% confidence interval (CI). EVIDENCE SYNTHESIS: The meta-analysis includes 6 cohort studies (1 prospective and 5 retrospective cohort studies) with a total of 9,662,088 individuals. We found that patients with PVCs have a significantly higher risk of AF than individuals without PVCs with the pooled RR of 1.90 (95% CI: 1.51-2.39, I2=83%). CONCLUSIONS: PVCs are significantly related with a 1.90-fold higher incidence of AF, according to the present systematic review and meta-analysis. Nonetheless, further research is needed to determine how this connection should be treated in clinical practice if it is causal.